2006
DOI: 10.1136/qshc.2005.017525
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of health professionals who conducted root cause analyses after undergoing a safety improvement programme

Abstract: Background: Research on root cause analysis (RCA), a pivotal component of many patient safety improvement programmes, is limited. Objective: To study a cohort of health professionals who conducted RCAs after completing the NSW Safety Improvement Program (SIP). Hypothesis: Participants in RCAs would: (1) differ in demographic profile from non-participants, (2) encounter problems conducting RCAs as a result of insufficient system support, (3) encounter more problems if they had conducted fewer RCAs and (4) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 22 publications
5
75
0
Order By: Relevance
“…Our study adds to a growing body of research on the challenges of using RCA (Braithwaite et al, 2006;Wu et al, 2008;Tamuz et al, 2011). We find that in practice difficulties arise at several stages of the RCA process.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our study adds to a growing body of research on the challenges of using RCA (Braithwaite et al, 2006;Wu et al, 2008;Tamuz et al, 2011). We find that in practice difficulties arise at several stages of the RCA process.…”
Section: Discussionmentioning
confidence: 79%
“…For instance, Braithwaite et al (2006) report that their Australian informants often viewed RCA processes as limited by time constraints, lack of expertise, and difficulties of working with colleagues. Wu et al (2008), examining the use of RCA in North America, show that there are inherent difficulties in translating RCA recommendations into tangible service change.…”
Section: Root Cause Analysis In Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…These discussions contribute to openness and trust. 44,45 Indeed, in this study, participants indicated that discussions around reports helped them remain aware of incidents and to address each other regarding safety issues during daily practice. In this way, safety management was embedded in everyday work.…”
Section: 41mentioning
confidence: 82%
“…10 In a survey of professionals conducting RCAs, 69.2% felt their recommendations were at least partly implemented. 12 Not all actions aimed to mitigate risk are equal. Some actions, like redesigning a product or process, are strong and have a high probability of reducing harm.…”
Section: The Root Cause Analysis Experiencementioning
confidence: 99%